The rise of Khārijism according to Abū Saʿīd Muḥ. b. Saʿīd al-Azdī al-Qalhātī - Kafafi, Muḥammad (Bulletin of the Faculty of Arts, 1952)
A short description of contents and abbreviated translation of the section that deals with the Khawārij from al-Qalhātī: al-Kashf wa’l-Bayān (MS in the British Museum, Or. 2606; see for a description Rieu 1894, 121-124). Wilkinson 1976a, 143: ... Thus one soon learns that Abū Saʿīd is inevitably Abū Saʿīd Muḥ. b. Saʿīd al-Kudamī and so could never be confused with Muḥ. b. Saʿīd al-Qalhātī, as the British Museum cataloguer (Sup. Cat. of Arab MSS, 1894, 121-124) has done.
Keywords: Kharijisme

الخوارج في الأندلس - مكي, محمود علي (تطوان : مجلة للأبحاث المغربية الأندلسية, 1956)
Keywords: Kharijisme

ثورات في المجتمع الإسلامي - حسن, محمد عبدالغني (الكتاب, 1953)
Keywords: Kharijisme

الخوارج في الإسلام - أبو النصر, عمر (مكتبة المعارف, 1956)
Abū ‘l-Naṣr, ʿUmar: (1956) al-Khawārij fī ‘l-Islām. Beirut: Makt. al-Maʿārif, 1956, (140 pp., 20x14 cm.).*
Keywords: Kharijisme